A Feminist Analysis of Katy Perry’s “Woman’s World” Lyrics and Music Video - Rafita Prasetya Ningsih; Krisna Sujiwa (Lingua Susastra, 2026)
Music videos and song lyrics function as cultural texts through which gender ideologies are both reinforced and contested. Despite growing interest in feminist media studies, few studies have integrated lyrical and visual analysis of contemporary pop music using Simone de Beauvoir's foundational concept of women as "The Other." This study analyzes how Katy Perry's 2024 song "Woman's World" represents female identity and women's empowerment through its lyrics and official music video. Employing a qualitative descriptive method grounded in de Beauvoir's The Second Sex (1949/2011), and supplemented by postfeminist media criticism, this study examines verbal and visual data,  including lyrics, costumes, body movements, and symbolic props through three analytical themes: the reversal of male-coded public spaces, female subjectivity, and symbolic resistance to gender stereotypes. The findings reveal that "Woman's World" constructs women as active, self-determining subjects who reject the subordinate position of "The Other" through dominant visual symbols and lyrical narratives. However, the analysis also identifies a recurring paradox in which feminist empowerment is simultaneously undermined by the entertainment industry's commodification of the female body. This study contributes to media feminist scholarship by demonstrating both the emancipatory potential and the commercial contradictions inherent in feminist representations within contemporary popular culture.